BIM-based space management system for operation and maintenance phase in educational office buildings - Ma, Guofeng; Song, Xue; Shang, Shanshan (Journal of Civil Engineering and Management, 2020)
Lists and floor plans have been widely adopted as space management tools for educational office buildings. However, the two-dimensional floor plans fail to present the indoor complexity, which hinders users from intuitively observing the indoor equipment arrangements and adapting to the indoor environment within a short time. Meanwhile, insufficient research has been conducted on space management tools regarding building indoor navigation. A Building Information Modeling Space Management (BIMSM) system was proposed in this study based on BIM. This system is comprised of two components, i.e. indoor space allocation management and indoor path navigation. The real-time space usage can be queried and user demands may be matched with available space by applying the Space Usage Analysis (SUA) theory. After the establishment of indoor maps, an improved A* algorithm is used to provide smooth navigation paths, and the visualization of such paths can be provided in mobile terminals. The BIMSM system was applied in an office building in a university in Shanghai, China. In this case study, the overall user satisfaction reached 91.6% by greatly reducing space arrangement failures. The time indoor navigation took outperformed that based on the traditional A* algorithm, with the search efficiency increasing 5.28%. First published online 17 December 2019